2005
DOI: 10.21236/ada462101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spacing and Geometry of Distributed Roughness Elements on a Two-Dimensional Turbulent Boundary Layer

Abstract: This thesis is a study of the effects of distributed roughness elements on a two-dimensional turbulent boundary layer. Measurements were taken on a total of ten rough wall configurations: four involving Gaussian spikes, and six with circular cylindrical posts. Rough wall flows are particularly suited to study with Laser Doppler Velocimetry (LDV) due to the fact that measurements are required near a solid surface, as well has in highly turbulent fluid. The LDV system used in this study is a fine resolution (≈ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The effect of structures on flow properties depends on their size, spacing, geometry and density (Wooding et al 1973, Stewart 2005, Frostick et al 2014. Here, controlling for density and biomass (size and geometry) revealed that spatial arrangement had no effect on mean instantaneous velocities over reef surfaces, although under fast flow conditions (48 cm s −1 ), velocities over randomly arranged mussels were up to 3.1 × faster than instantaneous velocities over clumped mussels; a difference not apparent under slow flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of structures on flow properties depends on their size, spacing, geometry and density (Wooding et al 1973, Stewart 2005, Frostick et al 2014. Here, controlling for density and biomass (size and geometry) revealed that spatial arrangement had no effect on mean instantaneous velocities over reef surfaces, although under fast flow conditions (48 cm s −1 ), velocities over randomly arranged mussels were up to 3.1 × faster than instantaneous velocities over clumped mussels; a difference not apparent under slow flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Bennington also studied the sweeping motion behind the element, the turbulent triple products, and made comparisons between elements with smooth edges and sharp edges. Stewart [20] and Varano [22] studied the effect of long fetches of sparsely spaced roughness elements. Stewart's roughness elements included…”
Section: Previous Researchmentioning
confidence: 99%
“…Further details about the seeding process can be found in Stewart (2005). These particles were injected in the wind tunnel upstream, right after the first contraction, before entering the test section.…”
Section: Third Generation Comprehensive Laser Doppler Velocimetermentioning
confidence: 99%